Low Threshold Microlasers Based on Organic-Conjugated Polymers - Chen, Hong-xu; Qian, Meng-dan; Yu, Kun; Liu, Yu-fang (Frontiers in Chemistry, 2021)
Conjugated polymers have emerged as ideal organic laser materials for the excellent optoelectrical properties and facile processability. Instead of simple film structures, resonator configurations with specific geometry are essential to provide optical feedback and then amplified light. Herein, we summarized the geometry and working mechanism of several typical resonator configurations formed with conjugated polymers. Meanwhile, recent advances in fabrication techniques and lasing performance are also discussed to provide new ideas for the design and optimization of microcavity geometries. Followed by the advances of practical applications in fields of laser sensing, bioimaging and laser illumination/display, we make a summary of the existing bottlenecks and future perspectives of electrically driven organic lasers towards laser display and illumination.